International Conference on Advanced Intelligent Systems for Sustainable Development (AI2SD'2023) Advanced Intelligent Systems on Energy, Environment and Agriculture, Volume 1 - Ezziyyani, Mostafa; Kacprzyk, Janusz; Balas, Valentina Emilia (Lecture Notes in Networks and Systems, 2024)
XII, 428 p. 165 illus., 139 illus. in color.